Effectiveness of the Active Cycle of Breathing Technique on Sputum Clearance and Airway Clearance in Patients with COPD: A Systematic Review - Mega Lybralia Permana; Agung Waluyo; Denissa Faradita Aryani (Indonesian Journal of Global Health Research, 2026)
The Active Cycle of Breathing Technique (ACBT) is a non-invasive technique for clearing the airways. It consists of three main components: breathing control, thoracic expansion, and forced expiration techniques (huffing and coughing). This method is used in patients with lung disorders to reduce congestion, help expel secretions, increase oxygen flow to the lungs, and restore respiratory muscle function. This study aims to compare ACBT therapy in COPD patients with sputum excretion and airway clearance. A systematic review was conducted on 8 research articles from various databases such as ScienceDirect, Clinical Key, EBSCOhost, ProQuest, Sage Journals, Scopus, Cocharane, Mendeley. The selected research design used a randomized controlled trial and quasi-experimental between 2009 - 2023 with a sampling technique using purposive sampling, which discussed ACBT in COPD patients. Data were collected through a database search using the keywords (“Active Cycle of Breathing Technique” OR “ACBT”) AND (“Chronic Obstructive Pulmonary Disease” OR “COPD”). From 112 identified articles, 8 met the inclusion criteria and were reviewed using the Joanna Briggs Institute (JBI) Critical Appraisal Tool for quality assessment. The majority of studies have shown that ACBT significantly contributes to increased expected sputum volume, improved lung function (FEV1/FVC), increased oxygen saturation, and patient comfort and satisfaction. However, there are also some studies that show similar effectiveness between ACBT and other techniques such as the Flutter device or conventional therapy. ACBT is an effective, safe, and easy-to-do intervention, and can be an important part of the nursing management of COPD patients, especially in terms of airway clearance. The findings of this study support systematic data from previous studies on the impact of using ACBT to improve short-term airway secretion clearance. The effectiveness of ACBT in increasing the amount of sputum produced.